Diclofenac gel in the treatment of actinic keratoses - Nelson, Christopher G (Dove Medical Press, 2011)
Actinic keratoses are areas of intraepithelial neoplasia for which treatment is necessary. Because they arise in areas of sun damage, it is desirable to treat the entire damaged field to not only treat visible lesions, but also subclinical, emerging malignancies, ie, “field therapy”, 5-fluorouracil, imiquimod, and diclofenac are all treatment options, and are discussed and compared.